Comparison of Türkiye and south korea practices in preventing internet addiction - Bilge, Mehmet (Journal of Dependence, 2025)
Addiction is a phenomenon that has taken place and continues to take place in society in many ways from past to present. If we look at the phenomenon of addiction at the historical level, some artifacts found as a result of archaeological studies have shown that addictive substances existed in social, political, economic and religious life. The way in which addiction emerges varies in the light of the possibilities, technological developments and social events of the period. In today’s world, where behavioral addictions are newly addressed in the light of the developments, each country develops various methods of struggle. While developing these methods, countries take intensive or more basic measures in the light of their own variables. Internet addiction, which is a subheading of behavioral addiction, is a type of addiction that affects many countries today. This addiction, which is also seen among young people in Türkiye from time to time, many preventive measures are taken by both families and the state. Just like in Türkiye, it can be stated that this addiction has developed in South Korea and it is one of the countries where internet addiction has developed the most. South Korea, which had difficulty in dealing with this problem at the beginning of the process, has made great progress in preventing internet addiction and has become a country that has increased measures to prevent possible future problems. Since Türkiye is still at the beginning of the road in this regard, it has shortcomings. For this reason, in this study, protective-preventive practices for internet addiction in Türkiye will be discussed and a comparison will be made with South Korea, which has both great problems in this field and has realized many exemplary practices, and suggestions will be made on behalf of Türkiye.